Impact of cell balance on grid scale battery energy storage systems. (May 2020) - Fantham, Thomas L.; Gladwin, Daniel T.
Abstract: With the adoption of Lithium ion battery systems for grid scale storage, a better understanding of how these systems behave is becoming necessary in order to optimise their performance. Providing different grid services results in different types of power delivery — frequency response services result in varying depth, low power cycles, whereas other services such as arbitrage result in sustained delivery, generally at a higher power. The battery systems being used consist of a large number of cells where the variation and imbalance of these can cause operational issues. Using observed data from a grid connected 2MW / 1MWh battery system these issues are presented in this paper and a hypothesis is given. The observations are recreated under lab conditions using two different types of battery module allowing analysis at cell level. The results confirm the variation in cell behaviour at upper and lower states-of-charge and methods to mitigate are proposed.